2014
DOI: 10.1002/jsc.1963
|View full text |Cite
|
Sign up to set email alerts
|

Firm Performance and the Evolution of Cooperative Interfirm Networks: UK Venture Capital Syndication

Abstract: (2014) Firm performance and the evolution of cooperative interfirm networks: UK venture capital syndication. Strategic Change, 23 (12). pp. 107118., which has been published in final form at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Notably, though these powerful models have been in use for quite some time in the fields of sociology and education, their potential has yet to be fully realized in organizational scholarship. Applications of SAO models for co-evolution of networks and actor attributes in applied organizational settings include research examining the co-evolution of advice and leadership networks and (in)civility (Porath, Gerbasi, & Schorch, 2015), communication networks and perceived stress (Kalish et al, 2015), trust networks and job satisfaction (Agneessens & Wittek, 2008), interfirm networks and governance orientation (Benton, 2016), interfirm collaborative networks and firm performance (Checkley et al, 2014), status networks and peer control attempts (de Klepper et al, 2017), information sharing networks and evidence-based practice (Mercken, Saul, Lemaire, Valente, & Leischow, 2015), friendship networks and unethical behavior (Zuber, 2015) and advice, and friendship and difficult tie networks and psychological safety (Schulte et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, though these powerful models have been in use for quite some time in the fields of sociology and education, their potential has yet to be fully realized in organizational scholarship. Applications of SAO models for co-evolution of networks and actor attributes in applied organizational settings include research examining the co-evolution of advice and leadership networks and (in)civility (Porath, Gerbasi, & Schorch, 2015), communication networks and perceived stress (Kalish et al, 2015), trust networks and job satisfaction (Agneessens & Wittek, 2008), interfirm networks and governance orientation (Benton, 2016), interfirm collaborative networks and firm performance (Checkley et al, 2014), status networks and peer control attempts (de Klepper et al, 2017), information sharing networks and evidence-based practice (Mercken, Saul, Lemaire, Valente, & Leischow, 2015), friendship networks and unethical behavior (Zuber, 2015) and advice, and friendship and difficult tie networks and psychological safety (Schulte et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is a direct test of homophily. It has been used to test hypotheses such as high-performing firms cooperate with other high-performing firms (Checkley, Steglich, Angwin, & Endersby, 2014) or people seek advice from others with similar levels of psychological safety (Schulte et al, 2012). In our example, a significant positive parameter estimate would support Hypothesis 2, stating that people choose each other as friends because of similarity in their levels of turnover intentions.…”
Section: Modeling Steps In Rsiena: An Empirical Examplementioning
confidence: 99%
See 2 more Smart Citations
“…Previous research on the impact syndication networks have on the VC firm performances and results often shows positive links measured in terms of successful exit of the portfolio companies as well as internal rate of return on investment (Jääskeläinen, 2012;Guo & Jiang, 2013). It has been found that syndication can lead to better return and higher shareholder value (Brander et al, 2002;Lehman, 2006;Hochberg et al, 2007;Baraldi et al, 2012) and the network position of VC firms can also enhance their portfolio performance (Hochberg et al, 2007;Abel & Nisar, 2007;Checkley, Steglich, Angwin, & Endersby, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%